2008
DOI: 10.1144/sp304.2
|View full text |Cite
|
Sign up to set email alerts
|

Some first-order observations on magma transfer from mantle wedge to upper crust at volcanic arcs

Abstract: The viscosity of lavas erupted at volcanic arcs varies over orders of magnitude. A comparison of the relative abundance of viscous lava dome eruptions indicates that the average viscosity of arc lavas also varies considerably between arcs. It is shown that, for continental or transitional arcs with little within-arc crustal deformation and without underlying slab windows or tears, average lava viscosity is anticorrelated with average surface heat flux. The latter may be influenced by crustal thickness and crus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 63 publications
2
32
1
Order By: Relevance
“…Remobilization of shallow intrusives by fresh melt from greater depth is a common phenomenon for porphyritic lava domes (cf. Zellmer 2008Zellmer , 2009Kent 2014 and references therein), and some of the Tatun domes and viscous lava flows appear to conform to this petrogenetic scenario. As U -Th internal dating of major mineral phases is not possible on single mineral grains, but instead requires the analysis of bulk mineral separates, the obtained ages are likely to represent averages of a range of ages displayed by the mineral grains (cf.…”
Section: Discussionmentioning
confidence: 75%
“…Remobilization of shallow intrusives by fresh melt from greater depth is a common phenomenon for porphyritic lava domes (cf. Zellmer 2008Zellmer , 2009Kent 2014 and references therein), and some of the Tatun domes and viscous lava flows appear to conform to this petrogenetic scenario. As U -Th internal dating of major mineral phases is not possible on single mineral grains, but instead requires the analysis of bulk mineral separates, the obtained ages are likely to represent averages of a range of ages displayed by the mineral grains (cf.…”
Section: Discussionmentioning
confidence: 75%
“…Similarly, also Zellmer (2008Zellmer ( , 2009) based on global correlations between eruptive style, surface heat flux and convergence rates at different volcanic arcs, infers that the rate of melt production in the mantle wedge ultimately controls the deep dynamics of magma transfer.…”
Section: Felsic Magmasmentioning
confidence: 90%
“…For the subduction parameters, we use the convergence velocity data from Hughes and Mahood [] completed by Zellmer []; the subduction velocity, vertical descent velocity, and slabs' thermal parameter data from Lallemand et al . []; and the slab age, dip, and subduction duration data from Hughes and Mahood [].…”
Section: Geodynamic Parameters Tested For Control On Magma Ascent Andmentioning
confidence: 99%
“…Zellmer [] suggested that the melt production rates in the mantle influence the speed at which magma migrates through the crust. However, recent petrological and geophysical observations suggest that magma ascends in pulses of durations and volumes changing in time [ Druitt et al ., ; Parks et al ., ; John et al ., ], implying that ascent rates may be independent from production rates both in the crust and mantle.…”
Section: Introductionmentioning
confidence: 99%